Last King in India : Wajid Ali Shah. - Llewellyn-Jones, Rosie (Oxford : C. Hurst and Company (Publishers) Limited, 2014)
An affectionate biography of a much-maligned king who had the misfortune to be on the throne when the East India Company usurped power.
Cover -- Half-title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgements -- List of Illustrations -- Chronology -- Glossary -- Introduction -- 1. 'That Energetic Old Lady' -- 2. Pageants and Pantomimes -- 3. The Sorrows of Akhtar -- 4. The House of Fairies -- 5. At Garden Reach -- 6. A Tigress Escapes from the Menagerie -- 7. A Mimic Kingdom -- Conclusion -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: India - Oudh(Princely State).; Electronic books